A truncated p53 in human lung cancer cells as a critical determinant of proliferation and invasiveness - Weiying Li; Baitang Lai; Xuehui Yang; Chunyan Zhang; Hui Wang (Tumor Biology)
As a transcription factor, p53 must accumulate in the nucleus to be effective. Signals related to nuclear localization are distributed mainly in the C-terminal of p53. So these nuclear location domains were reserved and the other part of the C-terminal was removed in this study. We investigated whether the truncated p53 (p53(DEL)) may affect proliferation and invasive potential of human lung cancer cells. H1299 and 801D cells expressing full-length p53 and the p53(DEL) were obtained by screening. Cell proliferation assay, cell apoptotic analysis, cell migration assay, and invasion assay were performed. Protein expression was examined by Western blotting. The data showed H1299-p53(DEL) and 801D-p53(DEL) cells grew more slowly than H1299-p53 and 801D-p53 cells, respectively. The colony formation of H1299-p53(DEL) and 801D-p53(DEL) cells reduced. The truncated p53 induced cell apoptosis. The expression levels of Bax and p53 upregulated modulator of apoptosis were increased in H1299-p53(DEL) and 801D-p53(DEL) cells. H1299-p53(DEL) and 801D-p53(DEL) cells were also characterized by decreased migration and invasion. The expression of the truncated p53 resulted in upregulation of E-cadherin and downregulation of Vimentin, Slug, Twist1, and zinc finger E-box-binding homeobox 1, which suggested the truncated p53 inhibited epithelial–mesenchymal transition occurrence. The above-mentioned characteristics were reverted by treatment of with pifithrin-a, a p53 inhibitor. These findings support the existence of a direct link between the p53(DEL), proliferation, epithelial–mesenchymal transition, and invasiveness in human lung cancer cells. So the p53(DEL) is a promising target for prevention and treatment of lung cancer.